The structure in the Bagneres de Luchon and Andorra cross sections (Axial Zone of the central Pyrenees) - Clariana, P.; García-Sansegundo, J.; Gavaldá, J. (TRABAJOS DE GEOLOGÍA, 2009)
Two vertical different structural domains have been recognized traditionally in the Axial zone of the Pyrenees: i) infrastructure: a deep seated domain with medium to high metamorphic grade and main flat-lying foliation and ii) suprastructure: a shallow domain with lower metamorphic grade and main steep foliation. Different and contradictory interpretations have been proposed to explain this structural zonation. The cross sections constructed have allowed us to observe the features of the transition zone between both domains in the central part of the Axial Zone and propose a new deformational sequence with which the structures of both domains are related.